Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1210/en.2006-0845
|View full text |Cite
|
Sign up to set email alerts
|

Focal Adhesion Kinase and Paxillin: Novel Regulators of Brain Sexual Differentiation?

Abstract: Steroid-mediated sexual differentiation of the brain is a developmental process that permanently organizes the brain into a male or female phenotype. Previous studies in the rodent have examined the steroid-mediated mechanisms of male brain development. In an effort to identify molecules involved in female brain development, a high-throughput proteomics approach called PowerBlot was used to identify signaling proteins differentially regulated in the neonatal male and female rat hypothalamus during the critical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 36 publications
2
26
0
Order By: Relevance
“…[19]. FAK is generally high in the hypothalamus of neonatal female [35], and the decrease following estrogen treatment as is evident from the present results indicated that neonatal estradiol establishes irreversible masculinization and defeminization of the female rat brain. Granulin, a cytotropic factor was found to be increased in hypothalamus of male rats after neonatal estradiol treatment [36] but the significance of its increase in expression in POA in our study currently is not known.…”
Section: Brain Regions Preoptic Area Hypothalamus Pituitarysupporting
confidence: 71%
“…[19]. FAK is generally high in the hypothalamus of neonatal female [35], and the decrease following estrogen treatment as is evident from the present results indicated that neonatal estradiol establishes irreversible masculinization and defeminization of the female rat brain. Granulin, a cytotropic factor was found to be increased in hypothalamus of male rats after neonatal estradiol treatment [36] but the significance of its increase in expression in POA in our study currently is not known.…”
Section: Brain Regions Preoptic Area Hypothalamus Pituitarysupporting
confidence: 71%
“…Focal adhesions are multiprotein complexes that coordinate integrins, extracellular matrix proteins and the cytoskeleton (Harjanto and Zaman, 2010). Moreover, gender-selective differences in paxillin have been correlated with sexual differentiation in brain regions (e.g., hypothalamus) that develop perinatally in a sex-related manner (Speert et al, 2007). Some studies have reported gender-specific effects of early CPF exposures (Dam et al, 2000; Raines et al, 2001; Slotkin et al, 2001; Levin et al, 2001, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Although intron 1 includes a few CpG islands, there are 2 CpG islands around spot U7 (about 200 bp upstream and 100 bp downstream). The relation between estrogen and paxillin is not clear, but there is a report that in the hypothalamus of neonatal female rat, esradiol administration reduced the expression of paxillin and affected the brain sexual differentiation [42]. On the other hand, there are no genes around spot 10.…”
Section: Discussionmentioning
confidence: 99%